A Mirror for Recluses: A New Manuscript, New Information and Some New Hypotheses. (25th December 2014) - Jones, E. A.
Abstract : This note alerts the scholarly community to a newly-discovered manuscript of A Mirror for Recluses, a fifteenth-century English translation of the Latin rule for recluses, Speculum Inclusorum . The new manuscript includes substantial amounts of text that are missing from the only other extant copy, and it begins with a previously unknown translator's prologue. The latter (here transcribed in full) provides a date for the translation, and some substantial clues to provenance.